2021
DOI: 10.3390/pr9071174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of a Combined Tillage Implement with Plough and Rotary Tiller by Experiment and DEM Simulation

Abstract: In order to improve the performance of tillage tool for straw incorporation in silty clay loam, a combined tillage implement with plough and rotary tiller was designed. Its performance on straw incorporation and power consumption was investigated, and the combined tillage types (CTSR and CTDR) were compared with traditional tillage types including a sole plough type (SP and DP), a sole rotary tiller (RT), and a two-pass tillage type (SP+RT and DP+RT) in a rice field experiment. The effect of the forward speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…In the simulation experiment, contacts were established between three sets of parameters [31][32][33], including alfalfa and alfalfa, cast steel and alfalfa, and nylon and alfalfa. The material contact parameters were compiled from the literature [25] and are shown in Table 3.…”
Section: Simulation Test Of Grass-cutting Device 231 Simulation Model...mentioning
confidence: 99%
“…In the simulation experiment, contacts were established between three sets of parameters [31][32][33], including alfalfa and alfalfa, cast steel and alfalfa, and nylon and alfalfa. The material contact parameters were compiled from the literature [25] and are shown in Table 3.…”
Section: Simulation Test Of Grass-cutting Device 231 Simulation Model...mentioning
confidence: 99%
“…Energy consumption can be calculated during operation in order to create a tillage implement with minimal energy expenditure. Du et al [19] performed a theoretical analysis of the rotary tiller and validated it through discrete element simulation. The results showed that the research method is highly feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many articles are devoted to studying the performance and stability of tractors [10][11][12][13]. Improving the effectiveness of tillage is closely related to the characteristics of soil, and it is one of the areas that cannot be ignored [14][15][16]. There is a lot of research on autonomous driving [17][18][19][20][21], but there is very little on intelligent electric vehicles for unmanned driving in agriculture.…”
Section: Introductionmentioning
confidence: 99%